2011
DOI: 10.1038/jes.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thoracic and fine PM and their components on heart rate and pulmonary function in COPD patients

Abstract: Population-based personal exposures to particulate matter (PM) and personal-ambient relationships of PM and component concentrations for outpatients with COPD and/or asthma were investigated in New York City (NYC) and Seattle for thoracic PM (PM 10 ) and fine PM (PM 2.5 ). Measurements of outdoor, indoor, and personal PM 10 and PM 2.5 concentrations were made concurrently for 12-consecutive days at 24 patients' residences. Filters were analyzed for elemental components, using XRF and black carbon (BC), by refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Furthermore, the main living area may represent the location where subjects are awake and active, therefore having higher minute ventilation and increased particle deposition (32), and subsequently increased susceptibility to adverse effects of pollutant exposure. We found no link between pollutant concentrations and changes in lung function, similar to results of previous studies showing no clear association between indoor PM and lung function in few patients with COPD (27,28). NO 2 , a by-product of combustion with indoor sources including gas-burning appliances, may lead to worse respiratory health through airway epithelial damage, or lowering the threshold for viral-induced exacerbations (33,34).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the main living area may represent the location where subjects are awake and active, therefore having higher minute ventilation and increased particle deposition (32), and subsequently increased susceptibility to adverse effects of pollutant exposure. We found no link between pollutant concentrations and changes in lung function, similar to results of previous studies showing no clear association between indoor PM and lung function in few patients with COPD (27,28). NO 2 , a by-product of combustion with indoor sources including gas-burning appliances, may lead to worse respiratory health through airway epithelial damage, or lowering the threshold for viral-induced exacerbations (33,34).…”
Section: Discussionsupporting
confidence: 87%
“…A study including 35 subjects with COPD showed no association between indoor air quality and lung function, with no assessment of other clinical outcomes (27). Another small panel study including 17 subjects with COPD showed no association between PM 2.5 and PM 2.5-10 with lung function over 12 days (28). Our study addresses a significant gap in the evidence by investigating longitudinal health effects of indoor air quality in patients with COPD with repeated comprehensive clinical assessments, including lung function, respiratory symptoms, quality of life, and exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all subjects lived in the same campus and only temporal variations of PM 2.5 were concerned in this analysis. Further, with almost no indoor sources of PM 2.5 in their living places, fixed-sited measurements may serve as good surrogates of individual exposure to PM 2.5 and its components (Hsu et al, 2011;Janssen et al, 2005). Secondly, the statistical power of this analysis was limited due to the sample size; therefore, a larger study is still needed to confirm our results.…”
Section: Discussionmentioning
confidence: 81%
“…They also recorded the readouts of the cardiopulmonary function instruments used by the participants, 4 administered a brief questionnaire documenting ventilation status and potential indoor sources within the residences, and reviewed participants’ time-activity diaries from the previous 24 h.…”
Section: Methodsmentioning
confidence: 99%